Impact of fixture congestion on indices of performance & recovery in youth soccer players - Hattersley, C.; Wells, C.; Blagrove, R.; Trangmar, S.; Patterson, S. (Sport Performance & Science Reports, 2018)
Elite soccer schedules often require players to undertake two competitive fixtures within seven days. Previous research has reported that around 72-96 hours are required after a single soccer match for measures of muscle function to return to pre-game levels (1,2). As players are regularly required to complete periods where games are separated by only 48 to 72 hours contemporary research has started to investigate the e ects xture congestion has on elite senior players activity pro les and markers of recovery (3,4,5). However, it is apparent that there is a paucity of literature regarding the impact of fixture congestion in elite youth players (20). Aim. It is unclear how the exposure to two competitive fixtures within seven days a ects physical performance and recovery status in elite youth soccer players. The current study sought to identify if a di erence existed in indices of physical output and recovery during the second fixture in a double game week in comparison to a single game week.